Response of soil carbon fractions and enzyme activities to mowing management on in a coastal wetland of the yellow river delta - Cui, Qian; Yang, Hongjun; Wang, Guangmei; Ma, Jinzhao; Feng, Lu; Liu, Jingtao (Frontiers in Marine Science, 2022)
Coastal wetlands are considered as important “blue carbon” sink, and mowing management induced by anthropogenic activities is anticipated to profoundly affect soil carbon stocks in coastal wetlands. However, the impacts of mowing management on soil organic carbon (SOC) and enzyme activities and the mechanisms responsible for associated changes in Phragmites australis wetland remain uncertain. We conducted a field mowing manipulation experiment [control (CK), mowing and returning straw in December (12MS), mowing and removing straw in December (12MR), mowing and returning straw in March (3MS), and mowing and removing straw in March (3MR)] in P. australis wetland of the Yellow River Delta and quantified their impacts on soil quality, SOC, SOC fractions, and enzyme activities. Results showed that mowing treatments led to overall increases in soil nutrients [total carbon (TC), total nitrogen (TN), total phosphorus (TP), NH4+, and NO3−] and decreases in soil C/N ratio. The effects of mowing treatments on soil nutrient content were pronounced on topsoil than deep soil, and the maximum value of TC, TN, and TP reached in the 12MR treatment. Compared with CK, the 12MS, 12MR, 3MS, and 3MR treatments at 0–10 cm depth significantly enhanced SOC content by 8.78%, 32.9%, 16.5%, and 30.1%, respectively, but only the 3MS treatment enhanced SOC by 16.5% at 10–20 cm depth. Mowing treatments increased dissolved organic carbon (DOC), microbial biomass carbon (MBC), particulate organic carbon (POC), and labile organic carbon (LOC) and the contents of DOC, MBC, POC, and LOC decreased with soil depth. Mowing treatments stimulated the activities of sucrase and urease in topsoil, but only the 3MR treatment improved alkaline phosphatase activity in topsoil. Path analysis indicated that mowing management dominantly modulates SOC by changing sucrase activity, alkaline phosphatase activity, TN, TP, NH4+, NO3−, DOC, and LOC in 0–10 cm depth. However, SOC was significantly controlled by sucrase activity, urease activity, TC, TN, TP, LOC, and POC in 10–20 cm depth. Collectively, our results indicate that the continuous mowing management is beneficial to enhance soil quality and carbon storage capacity of P. australis wetlands, which will contribute to enhance carbon sequestration and sink capacity of coastal wetlands.